Enhanced SNAr triggered ESIPT to ultrafast NIR fluorescent detection hazardous thiophenols class in environment and living cells. (October 2020) - Ren, Haixian; Huo, Fangjun; Huang, Yongfei; Chao, Jianbin; Wen, Wei; Fan, Jianfeng; Yin, Caixia
Abstract: Thiophenols are an important class of raw material and intermediate to prepare pesticides, medicines and polymers in chemical industry. However, they are highly toxic and harmful to the organisms and the environment, evaluated as No. P014 acute hazardous waste by USEPA (the environmental protection agency in US). Despite establishing the permittable discharge standards, thiophenols still bring about a threat to the environment primarily due to the absence of reliable and convenient detection methods. In this study, 2, 4-dinitrobenzenesulfonyl (DNPS) was introduced to enhance S N Ar, then ESIPT of the fluorophore was triggered quickly by 'enhanced S N Ar' between the probe and strongly nucleophilic thiophenols, thus NIR ultrafast thiophenols detection was realized. The probe was able to detect the 4-methyl thiophenol (MTP) within 13 s with the limit of detection (LOD) of 13.3 nM (below the exposure limit of 0.5 ppm provided by the National Institute for Occupational Safety and Health (NIOSH)). More, the probe was successfully applied to monitor the levels of the thiophenols in environmental water samples and Hela cells. Graphical abstract: Image 1 Highlights: Enhanced S N Ar was designed by introducing strong electron-withdrawing group. Enhanced S N Ar triggering ESIPT realized ultrafast NIR fluorescent detection for hazardous thiophenols. The probe could be used in detection of hazardous thiophenols in environment and living cells.